The Role of Registers in Increasing Knowledge and Improving Management of Children and Adolescents Affected by Familial Hypercholesterolemia: the LIPIGEN Pediatric Group - Gazzotti, Marta; Casula, Manuela; Bertolini, Stefano; Capra, Maria Elena; Olmastroni, Elena; Catapano, Alberico Luigi; Pederiva, Cristina, the LIPIGEN Paediatric Group; Allevi, Massimiliano; Arca, Marcello; Auricchio, Renata; Averna, Maurizio; et al. (Frontiers in Genetics, 2022)
Pathology registers can be a useful tool to overcome obstacles in the identification and management of familial hypercholesterolemia since childhood. In 2018, the LIPIGEN paediatric Group was constituted within the Italian LIPIGEN study to focus on FH subjects under 18 years. The present work aimed at discussing its recent progress and early outcomes. Demographic, biochemical and genetic baseline characteristics were collected, with an in-depth analysis of the genetic defects. The analysis was carried on 1602 children and adolescents (mean age at baseline 9.9±4.0 years) and almost the whole cohort underwent the genetic test (93.3%). Overall, the untreated mean value of LDL-C was 220.0±97.2 mg/dL, with an increasing gradient from subjects with a negative (N=317; mean untreated LDL-C = 159.9±47.7 mg/dL), inconclusive (N=125; mean untreated LDL-C = 166.4±56.5 mg/dL) or positive (N=1053; mean untreated LDL-C = 246.5±102.1 mg/dL) genetic diagnosis of FH. In this latter group, the LDL-C values presented a great variability based on the number and the biological impact of involved causative variants. The LIPIGEN pediatric group represents one of the largest cohorts of children with FH, allowing to deepen the characterization of their baseline and genetic features, providing the basis for further longitudinal investigations for full details.